Social Work and Nursing staff Perceptions of the Social Determinants of Health Based on Practice - Ekhlas Waheed Tokhi,; Ahmed Abdullah Sahli Al-Ruwais Al-Otaibi,; Sultan Mataab Nahad Alosaimi,; Mohammad Abdulaziz Saad Algwai,; Wasayf Naif Eqab Alhammadi,; Aljwharah Gaed Alosaimi,; Tahani Khaled Alotaibi,; Hanan Dhidan Shamruk Alotaibi,; Rahmah Mohammed Ali Asiri,; Nada Saeed Alblwi,; Hind Saad Aljuaid,; Mohammed Alosh Aid Alotiby, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Research indicates that poorer and less educated individuals have higher rates of health issues and mortality compared to those with higher levels of education. This disparity persists even in wealthy countries such as Saudi Arabia. Aim of the study :Explore the social determinant of health practices among social workers and nursing staff Methods: Research design: Descriptive cross-sectional research design was utilized. Setting:it was conducted in five large hospital, with bed capacity 250. they provide healthcare for paid and free services Participant: It includes 350 participant (nurses and social worker) who accept to be apart in the study and had experience less than 6 months experience. Instrument: One tool was utilized: Social determinant of health: it consist of two parts It consist of 33questions , the participant choose the most appropriate answer question according to their perception Results: The findings indicate that social workers generally have a higher level of awareness and recognition of SDOH compared to nurses.Healthcare Access & Quality is perceived as a key determinant by both groups, with 90% of nurses and 95% of social workers acknowledging its significance. This suggests a strong understanding of the direct impact of healthcare access on patient outcomes.Economic Stability is recognized by 60% of nurses but by a significantly higher 90% of social workers. This discrepancy suggests that nurses may be less attuned to the financial barriers affecting patient health.Education Access & Quality is acknowledged by 75% of nurses and 80% of social workers, reflecting general agreement on the role of education in health literacy and outcomes.Neighborhood & Built Environment shows the largest gap, with only 50% of nurses recognizing its importance compared to 85% of social workers. This may indicate that nurses focus more on clinical aspects rather than broader social conditions.Social & Community Context is more widely recognized by social workers (87.5%) compared to nurses (65%), likely due to their training in social systems and support structures. Conclusion: Nursing education should cover social determinants of health to coincide with social workers' perspectives. Hospitals and healthcare organizations should offer collaborative training sessions for nurses and social workers on SDOH. Healthcare facilities should create policies to encourage nurses to participate in community health projects.